Tinjauan Kedwibahasaan Buku Cerita Anak ‘The Foos’ dari Pandangan Metode Penerjemahan - Mardliyah, Aisyah; Engliana, Engliana; Supadi, Supadi (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2024)
Bilingual children's story books in Indonesian and English are now being published in Indonesia, providing them as reading options for mothers, caregivers, storytellers, and the children themselves. This study aims to analyze, identify, describe, and classify the forms of translation methods found in a bilingual children's storybook entitled 'The Foos' by Arleen Amidjaja, as well as to analyze the translation methods applied to determine the success in achieving equivalence of meaning in the target language (TL). This study uses a qualitative descriptive method and a documentation method. Employing text analysis, careful reading, and note taking techniques for research constitutes the stages of data collection. Text analysis uses Newmark's translation method theory with data sources from English texts as the source language text (SL) and Indonesian as the TL from the storybook 'The Foos.' The results of the analysis are presented in the form of a comparison of the two languages ​​, along with the results of identifying SL and TL text translation techniques. The interpretation of the identification results is then presented in the form of a descriptive presentation by considering the translation techniques of the identification results. The results of this study indicate that 12 translation method data are oriented to the SL, and eight are oriented to the TL. The translation techniques that are often used are semantic and communicative translation techniques. There are no faithful, adaptation, or idiomatic translation techniques because the children's storybook 'The Foos' does not have proverbial sentences or other foreign language terms. The SL uses simple sentence structures and vocabulary. The translation method that is oriented to the SL with semantic and communicative translation techniques is effective for translating children's storybooks, ensuring that readers understand the content of the stories.